In vitro colonic catabolism of orange juice (poly)phenols. Issue 3 (22nd January 2015) - Pereira‐Caro, Gema; Borges, Gina; Ky, Isabelle; Ribas, Aleix; Calani, Luca; Del Rio, Daniele; Clifford, Michael N.; Roberts, Susan A.; Crozier, Alan
<x xml:space="preserve">Abstract</x> Scope The role of colonic microbiota in the breakdown of hesperetin, naringenin, and ferulic acid, compounds found as glycosides in orange juice, was investigated using an in vitro fermentation model. Methods and results Test compounds were incubated with human fecal slurries cultured under anaerobic conditions, and the production of phenolic acid catabolites were monitored by GC‐MS and HPLC‐MS2. Hesperetin was converted to 3‐(3′‐hydroxy‐4′‐methoxyphenyl)propionic acid, 3‐(3′, 4′‐dihydroxyphenyl)propionic acid, and 3‐(3′‐hydroxyphenyl)propionic acid while 3‐(phenyl)propionic acid was the major end product derived from naringenin. The data obtained are compared to our previously published data on urinary excretion of phenolic and aromatic acids after acute orange juice consumption (Pereira‐Caro et al. Am. J. Clin. Nutr. 2014, 100, 1385–1391). Catabolism pathways are proposed for events occurring in the colon and those taking place postabsorption into the circulatory system with particular reference to the excretion of 3‐(3′‐hydroxy‐4′‐methoxyphenyl)hydracrylic acid, which is not formed in fecal incubations. Ferulic acid was also degraded by the colonic microflora being converted principally to 3‐(3′‐methoxy‐4′‐hydroxyphenyl)propionic acid, a phenolic acid that appears in urine after orange juice consumption. Conclusion The study provides novel information on the potential involvement of the colonic microbiota in the overall bioavailability of orange juice (poly)phenols through the production of phenylpropionic acids and subsequent hepatic conversions that lead to hippuric acid and its hydroxylated analogues.